AN ATTITUDE CONTROL LAW A SPACE CRAFT BASED ON SWITCHING FUNCTION SELECTION (Sciences & Technologie. B, Sciences de l'ingénieur, 2017)
This paper addressed the problem of nonlinear attitude control for a rigid satellite using a sliding mode control, in which the output function to be tracked is the quaternion attitude parameter. A sliding mode controller has been designed to force the state variables of the closed loop system to converge to the desired values with discussing the two cases.The proposed approach is defined in such a way that the selected controller parameters can drive the state to hit the sliding surface and keep it in this state. The controller is also simplified with stable tracking performances. The basic design of the controller is presented in this paper, and simulation results show that precise attitude control is accomplished in spite of the uncertainty in the system.